Implementation of Integrated Hygiene Education for the Prevention of Soil-Transmitted Helminths in Young Children - Dhito Dwi Pramardika; Meityn Disye Kasaluhe; Grace Angel Wuaten; Mareike Doherty Patras; Getruida Nita Mozes; Agneta Sartika Lalombo (Universitas Putra Indonesia YPTK Padang, 2026)
Screening for soil-transmitted helminth (STH) infection in preschoolers living in endemic regions demands a multimodal approach that incorporates fecal examination, child-targeted educational games, and parental involvement. This descriptive study involved children attending PAUD 3 Bahasa Biji Sesawi, Tahuna, Sangihe Islands on October 1, 2025. Eight children aged 3–6 years participated in this integrated intervention, which consisted of multimodal education through chants, visual quizzes, video watching, hands-on practice for handwashing technique, parasitological examination using the flotation method, and parental education. Post-intervention assessment showed a significant increase in the percentage of children performing the six-step handwashing technique correctly, from 25% to 87.5%. The percentage of parents categorized as having good knowledge also increased from 37.5% to 87.5%. Of the small number of samples examined, the positivity rate of the parasitological examination for hookworm eggs was 12.5 %. This study implies that the incorporation of parasitological observations as part of health education interventions for preschoolers could be used as a behavior modification trigger, despite operating under limited facilities. The approach is feasible as a pilot model of integrated hygiene education intervention for preschoolers that shares epidemiological characteristics